Nebivolol treatment increases splanchnic blood flow and portal pressure in cirrhotic rats via modulation of nitric oxide signalling. (20th January 2013) - Reiberger, Thomas; Payer, Berit Anna; Schwabl, Philipp; Hayden, Hubert; Horvatits, Thomas; Jäger, Bernhard; Hummel, Thomas; Mitterhauser, Markus; Trauner, Michael; Fuhrmann, Valentin; Angermayr, Bernhard; Peck‐Radosavljevic, Markus; et al.
Abstract Background We evaluated the effects of nebivolol, a third generation beta‐blocker capable of increasing NO‐bioavailability on portal pressure, and on splachnic and systemic haemodynamics in a cirrhotic portal hypertensive rat model. Methods Male Sprague–Dawley rats underwent sham operation (SO) or bile duct ligation (BDL). When cirrhosis was fully developed, the animals were orally treated with low‐dose (5 mg/kg) or high‐dose (10 mg/kg) nebivolol (NEBI) or vehicle (VEH) for 7 days. Heart rate (HR), mean arterial pressure (MAP), portal pressure (PP) and superior mesenteric artery blood flow (SMABF) were measured. Portosystemic collateral blood flow (PSCBF) was quantified using radioactive microspheres. Hepatic and splanchnic NOx levels and GSH/GSSG ratios (RedOx state) were determined using commercially available kits. Results BDL‐VEH rats showed increased HR, PP and PSCBF, whereas MAP was decreased compared to SO‐VEH rats. Nebivolol significantly reduced HR both in SO (P < 0.001) and BDL (P < 0.001) rats. BDL‐NEBI animals had significantly higher PP (15.5 vs. 12.6 mmHg; P = 0.006) and SMABF (5.3 vs. 3.7 ml/min/100g; P = 0.016) than BDL‐VEH animals. The increase in PP and SMABF was noted both in low‐dose and high‐dose BDL‐NEBI rats. While no beneficial effects on hepatic RedOx state were observed, splanchnic NOx levels were significantly increased by NEBI treatment in a dose‐dependent manner. Nebivolol treatment did not affect PSCBF in SO and BDL animals. Conclusion Nebivolol increases portal pressure in cirrhotic animals by increasing splanchnic blood flow via modulation of NO signalling. Porto‐systemic collateral blood flow remained unchanged. These data do not support the use of Nebivolol for treatment of cirrhotic patients with portal hypertension.